The Effect of The Think Pair Share (TPS) Model on Increasing The Learning Activity of Living Things Cycle Material in Grade 4 Sd Negeri 001 Pujud Selatan Rokan Hilir - Syauqi, Muhammad; Mustika, Dea (Eduvest - Journal of Universal Studies, 2025)
The aim of this research is to determine the effect of the think pair share (TPS) model on increasing students' learning activeness in the material on life cycles in class 4 of SD Negeri 001 Pujud Selatan Rokan Hilir. The results of this research can be used as reading material, reference and as a guide for teachers and especially parents in practicing providing learning to their children. The method in this research is an experimental method with a one group pre test – post test design, namely one class as a control and experimental class. The data analysis technique used is quantitative data analysis. The results of this research are that there is a significant difference in students' activeness in learning science at SD Negeri 002 Pujud Selatan before and after using the think pair share (TPS) learning model. This can be proven by the results of hypothesis testing in the initial test (pre-questionnaire) using the independent sample test, obtaining a significance value of 0.358, which means 0.358 > 0.05, so Ho is accepted after being given treatment, so hypothesis testing is carried out in the final test (post-questionnaire). Using the Mann-Whitney test, a significance value of 0.000 is obtained, which means 0.000 < 0.05, so H1 is accepted, indicating that there is a significant influence, so it can be concluded that the application of the think pair share (TPS) learning model can increase students' active learning in science learning at school. base